Pengembangan Flashcard pada Gamifikasi Pembelajaran Biologi Materi Sistem Ekskresi di SMAN 2 Bukik Barisan - Lativa Qolbi; Heffi Alberida (LP2M UIN Ambon, 2026)
Learning media plays an important role in improving the quality of learning, but its use in schools is still limited and less interactive. This has an impact on low student engagement and conceptual understanding, especially in the excretory system material. This study aims to produce valid and practical gamification-based flashcard media. The method used is the 4-D model research and development (Thiagarajan, 1974) which includes the stages of define, design, develop,and disseminate. The research subjects consisted of two expert lecturers, one biology teacher, and 26 Phase F students at SMAN 2 Bukik Barisan. Instruments included observation questionnaires, validity, practicality, and reflection. The results showed that the media was very valid (91.78%) and very practical based on teacher (92.49%) and student (94.48%) responses.